An innovation in host responses to escalating genomic conflicts. - Martí, E.; Larracuente, A.M. (Trends in Genetics, 2025)
Conflicts between selfish elements and their hosts can trigger rapid structural and regulatory changes in genomes. Chen et al. discovered a novel species-specific innovation in response to a meiotic driver in Drosophila melanogaster. Their discovery highlights a new dimension in adaptive responses to selfish elements, with broad evolutionary consequences.